TANAH UNTUK KEADILAN SOSIAL : PERBANDINGAN PENATAAN DAN PENGATURAN PERTANAHAN DI BEBERAPA NEGARA - Imam Koeswahyono (Arena Hukum, 2019)
AbstractThe essential meaning of the comparison of land management system in several countries: China, Ghana, Ethiopia and Indonesia relates to ideas in the framework of social justice land arrangement in an effort to find similarities and differences between the laws of land being compared. In addition, it provides an objective rational explanation of the causes of differences both in philosophy, conception, legal politics, regulation and equality between land laws in the three countries. With a conceptual and comparative approach, using the theory of access to obtain justice, this study aims to broaden the horizons for the study of land law that philosophy and conception of national land law (HTN) based on Customary Law with methods of adaptation and integration of the philosophy of Pancasila into Customary law and law national land is a necessity so that the goal of reforming the national land law access to reform and asset reform can realize the essence of social justice.Â AbstrakMakna komparasi pengaturan penataan pertanahan di beberapa negara: Cina, Ethiopia, Ghana serta Indonesia berkaitan dengan ide/gagasan dalam kerangka penataan tanah yang berkeadilan sosial sebagai upaya mencari persamaan dan perbedaan di antara hukum tanah yang diperbandingkan. Di samping itu, memberikan penjelasan secara rasional obyektif penyebab terjadinya perbedaan baik secara falsafah, konsepsi, politik hukum, pengaturan dan persamaan di antara hukum tanah pada tiga negara tersebut. Dengan pendekatan konseptual dan komparatif, menggunakan teori akses untuk memperoleh keadilan, kajian ini bertujuan untuk memperluas cakrawala pandang bagi pengkajian hukum tanah bahwa falsafah dan konsepsi hukum tanah nasional (HTN) berbasis Hukum Adat dengan metode adaptasi dan integrasi filosofi Pancasila ke dalam hukum Adat dan hukum tanah nasional merupakan sebuah keniscayaan agar tujuan pembaruan hukum tanah nasional akses reform dan asset reform mampu mewujudkan esensi keadilan sosial.